1603 through the Eyes of Women Historians - Armel Dubois-Nayt (Etudes Epistémè)
This paper aims to compare women’s historical narratives on the year 1603 to those of men. Based on the writings of four early modern women, Arbella Stuart, Anne Clifford, Elizabeth Southwell and Margaret Hoby, it focuses on three major events : the death of Elizabeth Tudor, the beginning of the reign of James VI and the outbreak of Plague. It looks at the specificities of female voices on historical matters in terms of both tone and content whilst trying to account for them by looking at the particular writing conditions of each of these women. It also underlines the common interpretations these women shared with their male contemporaries on current affairs.